2001
DOI: 10.1080/010503901750069554
|View full text |Cite
|
Sign up to set email alerts
|

Speech-evoked cortical potentials recognition in cochlear implant users and speech

Abstract: Processing in the auditory cortex may play a role in the unexplained variability in cochlear implant benefit. P300 and N1/P2 were elicited in post-lingually deaf cochlear implant users wearing a Nucleus multichannel cochlear implant. Four sound contrasts were presented (500-1,000 Hz, /ba/-/da/, /ba/-/pa/ and /i/-/a/). N1 and P2 were present in all subjects for all conditions. Prolonged N1, P2 and P300 latencies were found in the cochlear implant group compared to a control group of subjects with normal hearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
65
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 7 publications
7
65
0
5
Order By: Relevance
“…In contrast to previous studies (Beynon et al, 2005;Groenen et al, 2009), our participants could not rely on perceptual discrimination alone but had to identify the meaning of the two-syllabic words. Our results revealed poorer speech intelligibility in CI users than in NH listeners and group-specific modulation effects of ERPs as a function of background noise.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast to previous studies (Beynon et al, 2005;Groenen et al, 2009), our participants could not rely on perceptual discrimination alone but had to identify the meaning of the two-syllabic words. Our results revealed poorer speech intelligibility in CI users than in NH listeners and group-specific modulation effects of ERPs as a function of background noise.…”
Section: Discussionmentioning
confidence: 97%
“…Central auditory and cognitive processing in CI users has been usually examined by means of the oddball paradigm (Beynon et al, 2005;Groenen et al, 2009;Henkin et al, 2009). Here, the participants are presented with infrequent stimuli deviating in some physical or higher-order feature from regular standard sounds (Donchin and Coles, 1998;Polich, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potentials were elicited by pairs of stimuli, that differed by a vowel contrast (/da/ vs. /di/) [Micco et al, 1995] or by a consonant contrast (/da/ vs. /ta/) [Kraus et al, 1993]. Groenen et al [2001] and Beynon et al [2005] recorded the P3 potential in adult CI recipients and showed that while a vowel discrimination task (/i/ vs. /a/) elicited P3 potentials similar to those of NH subjects, consonant discrimination tasks (/ba/ vs. /pa/, /ba/ vs. /da/) yielded a smaller, prolonged, or absent P3. The fact that P3 of CI recipients was similar to that recorded from NH subjects in the easier vowel discrimination task suggests that these stimuli may not be sensitive to the differences in central auditory processing between the two groups.…”
mentioning
confidence: 99%
“…4,5 Kortekste bilinç seviyesinde oluşan bu potansiyel, dikkat, hafıza gibi bilişsel fonksiyonlardan etkilenmektedir. 6,7 Üst seviyede bilişsel işlemi yansıtan P300 yanıtı, normal işiten ve işitme cihazı/koklear implant kullanan kişilerin işitsel hafıza, işitsel ayırt etme becerilerinin ve konuşma performanslarının değerlendirilmesinde önemli bir yer tutmaktadır. 8 Odyolojide, farklı "sinyal/gürültü oran (SGO)'larında farklı tipte gürültü verilerek santral işitme sisteminin fonksiyonları değerlendirilmek-tedir.…”
unclassified